STRATIGRAFI DAN SEDIMENTOLOGI ENDAPAN DATARAN PASANG-SURUT DI KALI TULIS, BANJARNEGARA - Bachri, Syaiful; Slameto, Edi; Nurdiana, Indra (Jurnal Geologi dan Sumberdaya Mineral, 2010)
The tidal flat deposits of the Merawu Formation in Kali Tulis belongs to the Merawu Formation, and can be divided into two members, i.e. the lower part or the mudstone member, and the upper part or the sandstone member, with gradational contact between the two members. The lower parts is dominated by mudstone which is mostly deposited in mud flat environment, while the upper part is dominated by sandstone which is dominantly deposited in sand flat environment. Some sandstone layers in the lower part contains foraminifers of Early – Middle Miocene age, whereas the occurrence of fossils in the upper part has not been known so far. Sedimentary structures found in the two members include herring-bone structure, small scaled slump, parallel and cross laminations, bioturbation, flute cast, bed load, and fining upwards grain size. The sandstone of the two members contains volcanic rock fragments abundantly, suggesting that the provenance is volcanic rock in volcanic arc.Keywords: sand flat, mud flat, herring bone structure, Merawu Formation